Faktor-Faktor Yang Memengaruhi Implementasi Sistem Informasi Manajemen Rumah Sakit Di RS. Nurul Hasanah Aceh Tenggara - Salmiati Salmiati; Juliandi Harahap; Deli Theo (Jurnal Kesehatan dan Fisioterapi, 2023)
Abstract- Hospital manajemen information systemswas an integrated information system prepared to handle the entire hospital management process. This study aimed to analyze the factors that influence the implementation of the Hospital Management Information System in Nurul Hasanah Hospital. The research design used a kuantitatif method. The sample of this study was 43 used total sampling. The research data were analyzed by univariate, bivariate and multivariate. Based on the results of quantitative research at the univariate stage, it was known that of the 43 respondents, most of them are 36-45 years old, namely 21 (48.8%), with an undergraduate education level of 24 (55.8%). Bivariate results show that there was an influence of human resources (p=0.011), organization (p=0.010), technology (p=0.005) on the implementation of hospital management information systems in Nurul Hasanah hospital. The conclusion is that there is an influence of human resources, organization, technology on the implementation of hospital management information systems in Nurul Hasanah hospital and the most influential variables in the hospital management information system at the Nurul Hasanah was a technology variable. Suggestions in this study so that the results of this study can be used as input and evaluation material for hospital management to improve human resources by conducting continuous training for employees.